Iron And Manganese Removal From Groundwater By Using Limestone Filter With Iron-Oxidizing Bacteria - Tommy, Huang Lick Wei (Universiti Sains Malaysia, 2019)
Groundwater is an important resource that can complement the increasing demand for fresh water needs. It is abundant in many areas; unfortunately, it commonly presents with iron (Fe) and manganese (Mn) which requires further treatment process to ensure the water quality is acceptable. The main objective of this research was to evaluate the performance of the groundwater treatment using limestone filter alone and limestone assisted with iron-oxidizing bacteria (IOB) found at the Kampung Chap Water Treatment Plant, Kelantan. IOB has been used at the treatment plant, immobilized on the surface of the sand filter. Limestone with the particle size of range 0.6-2.36 mm was the host alternative to the IOB in this research. Limestone also acts as adsorption media as previous studies have indicated its capability in removing heavy metals. The groundwater sample from USM Borehole was first characterized. The comparisons of the treatment performances were made based on the filter column at a flow rate of 4.0 L/hour and retention time of 2.94 minutes. The result indicated that the 2.0 hours of operation time was the optimum running time for both treatment methods. With the 2.0 hours operation time, the percentage of Fe removal was 77.69% for limestone filter alone and 81.72% for limestone assisted with IOB, while the percentage of Mn removal was 82.60% for limestone filter alone and 83.63% for limestone assisted with IOB. Overall, the groundwater treatment by limestone assisted with IOB has better performance than the use of limestone filter alone. As the operation time increases, the performance of the treated groundwater is better. The IOB can catalyze the oxidation of soluble form of Fe (II) and Mn (II) to the insoluble form of Fe (III) and Mn (IV) respectively. It can be concluded that the presence of IOB is beneficial in improving the removal of Fe and Mn in the groundwater.